2013
DOI: 10.1177/0959651813483129
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm for parameter estimation of twin-rotor multi-input multi-output system using trust region optimization methods

Abstract: The twin-rotor, multi-input, multi-output system is a typical lab-scale helicopter system, since it resembles behavior of helicopter systems. This experimental complex aerodynamic test rig needs precise modeling to assure satisfactory control performance. Therefore, this article is intended to provide a gray-box approach for the modeling of the twin-rotor, multi-input, multi-output system. An algorithm is proposed by dividing the system into independent subsystems that can be estimated for an excitation input … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…The main and tail rotor BG models are shown in Figures 23 and 24, respectively. The drag and thrust forces due to the rotor are modeled therein as per equations (5)- (9). According to the relative motions between the rotors and the support beam, constraints are imposed at the joints.…”
Section: Modeling Of Jointsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main and tail rotor BG models are shown in Figures 23 and 24, respectively. The drag and thrust forces due to the rotor are modeled therein as per equations (5)- (9). According to the relative motions between the rotors and the support beam, constraints are imposed at the joints.…”
Section: Modeling Of Jointsmentioning
confidence: 99%
“…They found that both models give almost similar results; the Lagrangian model being marginally better than the Newtonian model. A gray box approach was proposed by Moness and Mostafa 9 for the modeling and identification of the TRMS using trust region optimization methods. They partitioned the TRMS into two decoupled subsystems and estimated the parameters of those subsystems independently for various input excitations.…”
Section: Introductionmentioning
confidence: 99%
“…The helicopter parameters were estimated by the authors in Moness and Mostafa (2013) and listed in Table 1. The non-linear model of the lab-scale helicopter system is linearized around the hovering point to obtain the transfer functions matrix described in Equation ( 8).…”
Section: Lab-scale Helicopter System Descriptionmentioning
confidence: 99%
“…In this setup, a substantially interconnected propeller, controlled by the main rotor, assumes the responsibility for stabilizing the platform's vertical orientation, effectively counteracting angular deviations along the vertical axis. Simultaneously, a smaller propeller, maneuvered by the tail rotor, enables precise adjustments along the horizontal axis [6,7]. The dynamic interplay of these configurations, whether quadrotor or twin-rotor, is regulated by intricate adjustments in pitch and yaw angles.…”
Section: Motivation and Introductionmentioning
confidence: 99%